The Revised Learning and Study Strategies Inventory: An Evaluation of Competing Models - Prevatt, Frances (Educ Psychol Meas, 2006)
Two competing structural models for the revised Learning and Study Strategies Inventory (LASSI) were examined. The test developers promote a model related to three uncorrelated components of strategic learning: skill, will, and self-regulation. Other investigators have shown empirical support for a three-factor correlated model characterized by effort-related activities, goal orientation, and cognitive activities (ER-GO-CA). Neither model has been verified on scores from the second edition of the LASSI. In the present sample of 297 college students, confirmatory factor analysis of the subscale scores provided support for the ER-GO-CA model.